2012
DOI: 10.1016/j.jsha.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of serum uric acid level in patients with acute ST elevation myocardial infarction

Abstract: Our data suggest that in the acute phase of ST elevation myocardial infarction, uric acid has a prognostic role for in-hospital and short-term (30-day) mortality in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…The inclusion criteria of 8 studies 18 - 20 , 23 , 24 , 26 - 28 were patients who were diagnosed with acute ST-elevation myocardial infarction (STEMI) and underwent PCI subsequently. The inclusion criteria of 2 studies 21 , 22 were patients with STEMI, but did not control their treatment plan. Another three studies 25 , 29 , 30 did not control whether these patients underwent PCI and included patients with STEMI and non-STEMI (NSTEMI) in the cohort.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria of 8 studies 18 - 20 , 23 , 24 , 26 - 28 were patients who were diagnosed with acute ST-elevation myocardial infarction (STEMI) and underwent PCI subsequently. The inclusion criteria of 2 studies 21 , 22 were patients with STEMI, but did not control their treatment plan. Another three studies 25 , 29 , 30 did not control whether these patients underwent PCI and included patients with STEMI and non-STEMI (NSTEMI) in the cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies (8521 participants) reported short-term mortality, wherein 2 studies 29 , 30 included patients with STEMI and NSTEMI in the cohort and did not control whether these patients underwent PCI; eight studies 18 - 20 , 23 - 28 included only patients with STEMI who underwent PCI. Two studies 21 , 22 included only patients with STEMI, but did not control whether these patients underwent PCI. The HSUA was associated with higher short-term mortality (RR=3.19, 95% CI: 2.68–3.79).…”
Section: Resultsmentioning
confidence: 99%
“… 8 In other study done in Iran higher serum UA had association with in-hospital and short term mortality. 9 By developing new treatments especially increasing trend to invasive therapy in high risk patients for example those who develop heart failure after ST-elevation myocardial infarction (STEMI) and continuous effort to decrease STEMI mortality, it is interesting to investigate whether prognostic factors such as serum UA continue to have their prognostic value or not.…”
Section: Introductionmentioning
confidence: 99%
“…High level of uric acid may exert a negative effect on the pathogenesis of CVDs by stimulating inflammation and oxidative stress ( Wang R. et al, 2016 ; Liu et al, 2017 ). Increased circulating uric acid level is recognized as a marker associated with acute ST-segment elevation myocardial infarction in patients ( Omidvar et al, 2012 ; Lazaros et al, 2013 ). Numerous studies have demonstrated that the enhanced inosine acts as a biomarker for acute cardiac ischemia, myocardial infarction in patients and animal models ( Fazekas et al, 1999 ; Farthing et al, 2007 , 2015 ).…”
Section: Discussionmentioning
confidence: 99%